Quantum spin tunneling in a soluble quasi-spin model: an angle-based potential description - Galetti, D.; Pimentel, B. M.; Lima, C. L. (Elsevier B.V., 2005)
We propose an approach which allows one to construct and use a potential function written in terms of an angle variable to describe interacting spin systems. We show how this can be implemented in the Lipkin-Meshkov-Glick, here considered a paradigmatic spin model. It is shown how some features of the energy gap can be interpreted in terms of a spin tunneling. A discrete Wigner function is constructed for a symmetric combination of two states of the model and its time evolution is obtained. The physical information extracted from that function reinforces our description of phase oscillations in a potential. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: spin tunneling; Wigner functions; Lipkin model